Maxent-based explanation of why financial analysts systematically under-predict companies’ performance - Vladik Kreinovich (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. Several studies have shown that financial analysts systematically under-predict the companies’ performance, so that quarter after the quarter, 70-75% of the companies outperform these predictions. This percentage remains the same where the economy is in a boom or in a recession, whether we are in a period of strong or weak regulations. In this paper, we provide a possible Maximum Entropy-based explanation for this empirical phenomenon – an explanation rooted in the fact that financial analysts mostly analyze financial data, while to get a more accurate prediction, it is important to go deeper, into the technical issues underlying the companies functioning.